Ensaios sobre migração interna de pessoas com alta instrução no Brasil - Santos, Weskla Barbosa dos (2013)
This dissertation aims to investigate the characteristics and trends of internal migration of people with high education in Brazil, trying specifically to identify regional patterns of skilled migration, its main determinants and the behavior of the "hourly wage" earned by migrants and non-migrants. Using the Census IBGE (Instituto Brasileiro de Geografia e Estatística) population for the years 2000 and 2010, the present research was divided in two trials. The first one evaluates routes performed by skilled migrants amid different territorial areas (regional, state, and meso-regional micro-regional) between the five-year periods 1995-2000 and 2005-2010. From it, the evidence shows that, in all areas analyzed, the South and Southeast regions have a higher amount of qualified people among its residents, as well as recorded the highest reception and issuing qualified in Brazil in both periods considered. Regarding the routes investigated, it has been established that most of the skilled returnees to their places of origin left the Northeast and Southeast regions, having as main target the Southeast. Also noteworthy agglomerations type high-high amid the North and Northeast to conduct a spatial analysis of Brazilian micro-regions during 2010, as agglomerations of type low-low are observed between the South and Southeast regions. The second essay, in turn, aims to analyze the joint determination of the decision to migrate and wages earned by workers with high education in Brazil. In this regard, it was noted that the skilled migrant is positively selected in unobserved productive attributes. Furthermore, when analyzing the group of migrants, it appears that men earn, on average, more than women (omitted category), those who declared themselves to black and brown have lower income compared to those reported color white (omitted category), the worker with a post-graduate degree has a higher "hourly wage" than the worker with a graduate degree and that unregistered workers as well as those of their own, have a lower yield than that acquired by the employee with formal contract. As variables considered location, one can ascertain that those living in urban areas earn an average "hourly wage" higher than those living in rural areas (omitted category). Just as those who reside in the metropolitan area and the North region states have higher income than those who live in non-metropolitan area (omitted category) and the state of São Paulo (omitted category), respectively. Now regarding the probability to migrate, it was observed that a man who holds graduate, live in the North and Southeast of the country and which has got a social networks, increase the chances of effecting skilled migration. In addition, there was a counterfactual exercise on income earned by migrants and non-migrants qualified in order to verify the rationality of the decisions of both groups. Thus, the results indicate that conferred the migrant has positive selectivity, since skilled workers who migrated recorded a higher hourly wage than those who did not migrate. Moreover, based on counterfactual exercise performed, ascertained that the choices made by both groups were rational, given that the income received was larger when considering the factual decisions (migrants - migrant and not migrated - not migrated) than observed when the counterfactual analysis (migrant - not migrated and non-migrant - migrated). Finally, one can still see that skilled workers who decided to migrate typically have the following characteristics: male, white, 36-years-old (on average), employed with contract, who lives in metropolitan urban areas and in the Southeast.